PEMBELAJARAN DARI PROJEK PERCONTOHAN REDD+ PADA FASE PERSIAPAN DAN KESIAPAN - Tien Wahyuni (Fakultas Seni Rupa dan Desain ITB, 2015)
Sejak 2008 Kementerian Kehutanan telah memulai program pengujian penerapan REDD+ di Indonesia melalui projek percontohan. Pada level subnasional, Kalimantan sangat relevan berkontribusi dalam mekanisme REDD+. Hal ini dibuktikan dengan tumbuhnya projek-projek yang mendukung kegiatan percontohan di Kalimantan. Projek-projek percontohan ini juga menjadi dasar pengujian untuk menjawab pertanyaan sebelum menyusun dan melaksanakan kebijakan REDD+ nasional di masa mendatang. Penelitian ini bertujuan untuk mendapatkan data, informasi, dan gambaran awal projek dan kegiatan percontohan REDD+ serta mengamati pola yang muncul dalam berbagai gambaran projek REDD+ di level subnasional dan implikasinya untuk mewujudkan REDD+. Penilaian dilakukan terhadap beberapa projek dan kegiatan percontohan REDD+ di Kalimantan berdasarkan dokumen projek serta wawancara semiterstruktur dengan para pemrakarsa projek dan pemangku kepentingan. Informasi yang tersedia dimaksudkan untuk memfasilitasi pemahaman dalam pembelajaran yang dapat digunakan untuk pembuatan rancang-an penelitian. Semua corak yang berbeda mengenai projek REDD+ di Kalimantan ini dapat memberikan pelajaran berharga untuk memanfaatkan hutan guna memperlambat perubahan iklim.Kata kunci : projek percontohan REDD+, kegiatan percontohan, kalimantanSince 2008 The Ministry of Forestry has been embarking on a program to test the implementation of Reducing Emission From Deforestation and Forest Degradation (REDD+) in Indonesia through a pilot project. At the sub-national level, the provinces of Kalimantan are the most relevant contributors to the REDD+ mechanism. It is proved with the growing projects which support the pilot activities in Kalimantan. These pilot projects also provide a basic test for answering some questions before structuring and implementing the national REDD+ policies. This study aims to obtain data, early information and description of REDD+ pilot projects and activities in Kalimantan, and to observe the emerging patterns in the sub-national landscape of REDD+ projects and its implications to realise REDD+. An assessment has been conducted to these REDD+ pilot projects and activities based on a review of project documents, semi structured interviews with project proponents and stakeholders. This available information is intended to facilitate understanding in the learning process and sharing of early lessons that can be used for designing future research on REDD+ pilots. All of these different patterns of REDD+ projects in Kalimantan can offer valuable lessons for harnessing forests to mitigate climate changes.Keywords: reducing emission from deforestation and forest degradation (REDD+), pilot projects and activities, kalimantan